Minority Stress or Gender Shift? Testing the Effect of Sexual Orientation on Psychological Distress Among Hong Kong Adolescents. - Ip, Ping Lam; Wong, Day; Fong, Ted C. T.; Chau, Eunice Y. M.; Yip, Paul S. F. (Sexuality & Culture, 2025)
The minority stress theory predicts that sexual minorities experience more psychological distress than heterosexual individuals because of stigma-related stress. However, the gender shift theory argues that sexual-minority females experience less distress than heterosexual females because the former's personality tends to shift in the male-typical direction and are less likely to possess neuroticism. We used a representative sample of Hong Kong secondary school adolescents (N = 6,725) to determine which theory would better explain the disparity in psychological distress between sexual-minority and heterosexual youth in the city. We conducted mediation analyses via structural equation modeling in the female sample (n = 2,984) and the male sample (n = 3,741) respectively. Our results support the minority stress theory, as sexual minorities of both sexes suffered from greater psychological distress as opposed to their heterosexual counterparts. Sexual orientation had a significant indirect effect on psychological distress via gender feeling, a measure of the extent to which individuals feel female or male. Sexual minorities who felt more like the opposite gender experienced more distress than their heterosexual counterparts. We also conducted an analysis of covariance to explore the between-group differences in psychological distress across sexual orientations in each sample. Our results show that bisexual/pansexual adolescents had significantly higher distress levels than their heterosexual and asexual counterparts.